More Important Than Ever: Embracing Digital marketing to Survive COVID-19 - Venkatesh Bala Sanger; Farah Waheeda Jalaludin; Tai Lit Cheng; Fitriya Abdul Rahim (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Businesses are most susceptible to the effects of Covid-19. The implementation of social distancing makes people limit activities outside their home, consequently sales turnover decreases. Therefore, SMEs need to change the mindset in running business by using technology transformation. The usage of digital marketing has proven to be more practical than traditional marketing at many times. The Movement Control Order (MCO) implemented on 18 March 2020 in Malaysia due to the pandemic has put a halt to businesses, thus crippling the income of those business owners. This study aimed to study how companies or businesses handle this crisis and how they are utilizing digital marketing to their benefit. The usage of three main types of digital marketing was investigated on the performance of companies or businesses in Malaysia during this pandemic. A total of two hundred and thirty-one questionnaires were collected from employees and employers who are working or have working experience. Three hypotheses were developed for each type of digital marketing on the performance of companies or businesses. The findings showed that many companies are benefiting from the adaptation of digital marketing during this pandemic. Data were analyzed using SmartPLS and revealed that social media marketing, email marketing and mobile marketing are effective for businesses to survive during this pandemic